G473 Outcomes of abo incompatible kidney transplantation in children. (27th April 2015) - Stojanovic, J; Mamode, N; Adamusiak, A; Knapp, K; Barton, C; Jones, HE; Taylor, J; Marks, SD
Abstract : Objective: ABO blood group incompatible transplantation (ABOi) has become increasingly common over the last decade, in part due to a shortage of suitable deceased donor allografts. Whilst encouraging data is emerging on short and medium term graft outcomes in adults, ABOi in children is rare; pre-transplant conditioning in paediatric patients remains challenging and concerns persist about an increased risk of rejection. Encouraged by good results in a large number of adult ABOi transplants, we extended our programme to paediatric recipients, and here report the largest European cohort. Methods: A retrospective analysis of all ABOi paediatric renal transplant recipients in the 2 largest centres in the UK sharing the same tailored desensitisation protocol. Patients with pre-transplant titres 1 in 8 or above received rituximab one month prior to transplant; tacrolimus and mycophenolate mofetil were started one week pre-op. Antibody removal was performed to reduce titres to 1 in 8 or less at surgery. No routine post-op removal was performed. Results: Ten children (age 2–14 years) underwent an ABOi kidney transplant (Figures 1 and 2 and Table 1 ). Graft and patient survival was 100%. Baseline titres, tailored desensitisation and graft outcomes are shown in table. One patient developed grade IIa rejection after 2 weeks successfully treated with anti-thymocyte globulin;no histological evidence of rejection in other 9 patients. Another patient had a rise in titre of 2 dilutions at week one treated with 2 immunoadsorption sessions. Nine patients had good graft function (eGFR 30–130 mls/min/1.73m2) at last follow up (range 1–36 months); one patient had eGFR 22 ml/min/1.73m2. One patient developed CMV and BK; another EBV and BK. Conclusion: ABOi transplantation in children appears to have an optimal outcome with good graft survival, low risk of rejection and infectious complications.